Characteristics of EGFR Mutations in Plasma Samples in Non-Small Cell Lung Cancer Patients after Treatment with 1st and 2nd Generation of TKI at Bach Mai Hospital - Thuan Loi, Nguyen; Cam Phuong, Pham; Dinh Hung, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
This study aims to describe EGFR mutation status detected in plasma samples and analyze some related factors in non-small cell lung cancer patients after treatment with the generation I and II Tyrosine Kinase inhibitors at Bach Mai Hospital. Patients and methods: A retrospective descriptive study on 75 patients with non-small cell lung cancer tested for EGFR mutations in plasma after treatment with 1st or 2nd EGFR -TKIs in 2019-2020. Results: EGFR mutations were detected in 97.3% plasma samples;  the T790M mutation accounted for  37.3% and is accompanied by a sensitive mutation TKI; The T790M mutations ratio after treatment was higher than before treatment with TKIs (p < 0.001); the median total duration of EGFR -TKI treatment was significantly longer in patients with T790M mutation than in those without (16.8 months vs 12.5 months, p = 0.005); the T790M mutation ratio was higher in patients with a deletion on exon 19 than in L858R mutation on exon 21 (p=0.028), in Erlotinib treatment group higher than in Gefitinib and Afatinib treatment group (51.4% vs. with 20.0% and 33.3%, p=0.039). Conclusions: EGFR mutation plasma test helps to monitor disease progression and detect resistance mutations T790M in NSCLC patients after TKI generation I and II. Keywords: non-small cell lung cancer, EGFR mutations, T790M mutations, TKIs.. References [1] H. Sung et al., Global Cancer Statistics 2020: GLOBOCAN Estimates of Incidence and Mortality Worldwide for 36 Cancers In 185 Countries, CA: A Cancer Journal for Clinicians. Vol. 71, No. 3, 2021, pp. 209-249, https://doi.org/10.3322/caac.21660. [2] N. V. Hieu, Oncology, Medical Publisher, 2015. [3] P. N. Ding et al., Plasma Pre-treatment T790M Relative Allelic Frequency in Patients with Advanced EGFR-mutated Non-small Cell Lung Cancer Predicts Treatment Response to Subsequent-Line Osimertinib, Translational Lung Cancer Research, Vol. 10, No. 4, 2021, pp. 1623-1634, https://doi.org/10.1186/s40169-020-0269-y. [4] N. Yamamoto et al., Erlotinib Plus Bevacizumab Vs Erlotinib Monotherapy as First-line Treatment for Advanced EGFR Mutation-positive Non-squamous Non-small-cell Lung Cancer: Survival Follow-up Results of the Randomized JO25567 Study, Lung Cancer, Vol. 151, 2021, pp.20-24, https://doi.org/10.1016/j.lungcan.2020.11.020. [5] D. S. Ettinger et al., NCCN Guidelines Insights: Non–Small Cell Lung Cancer, Version 2, 2021: Featured Updates to the NCCN Guidelines", Journal of the National Comprehensive Cancer Network, Vol. 19, No. 3, 2021, pp. 254-266, https://doi.org/10.6004/jnccn.2021.0013. [6] K. Usui et al., Plasma ctDNA Monitoring During Epidermal Growth Factor Receptor (EGFR)-Tyrosine Kinase Inhibitor Treatment in Patients With EGFR-mutant Non-small Cell Lung Cancer (JP-CLEAR trial), Japanese Journal of Clinical Oncology, Vol. 49, No. 6, 2021, pp. 554-558, https://doi.org/10.1093/jjco/hyz023. [7] M. Nagasaka et al., Liquid Biopsy for Therapy Monitoring in Early-stage Non-small Cell Lung Cancer, Molecular Cancer, Vol. 20, No. 1, 2021, pp. 82, https://doi.org/10.1186/s12943-021-01371-1. [8] M. D. Re et al., Incidence of T790M in Patients with NSCLC Progressed to Gefitinib, Erlotinib, and Afatinib: A Study on Circulating Cell-free DNA, Clinical Lung Cancer, Vol. 21, No. 3, 2020, pp. 232-237, https://doi.org/10.1016/j.cllc.2019.10.003. [9] S. Jenkins et al., Plasma ctDNA Analysis for Detection of the EGFR T790M Mutation in Patients with Advanced Non–small Cell Lung Cancer", Journal of Thoracic Oncology, Vol. 12, No. 7, 2017, pp. 1061-1070, https://doi.org/10.1016/j.jtho.2017.04.003. [10] R. Ko et al., Frequency of EGFR T790M Mutation and Multimutational Profiles of Rebiopsy Samples from Non-small Cell Lung Cancer Developing Acquired Resistance to EGFR Tyrosine Kinase Inhibitors in Japanese Patients, BMC Cancer, Vol. 16, No. 1, 2016, pp. 864, https://doi.org/10.1186/s12885-016-2902-0. [11] N. Matsuo et al., Association of EGFR Exon 19 Deletion and EGFR-TKI Treatment Duration with Frequency of T790M Mutation in EGFR-Mutant Lung Cancer Patients, Scientific Reports, Vol. 6, No. 1, 2016, pp. 36458 , https://doi.org/10.1038/srep36458. [12] W. Fanget al., EGFR Exon 20 Insertion Mutations and Response to Osimertinib in Non-small-cell Lung Cancer, BMC Cancer, Vol. 19, No. 1, 2019, pp. 1-9, https://doi.org/10.1186/s12885-019-5820-0. [13] D. T. Hien, P. C. Phuong, Analysis of EGFR Mutations in Paraffin-covered Tissue Samples and some Related Factors from Non-small Cell Lung Cancer Patients Over 60 Years Old, Science and Technology Vietnam, Vol. 62, No. 7, 2020, pp. 1-5 [14] S. Hong et al., Concomitant Genetic Alterations with Response to Treatment and Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Patients with EGFR-Mutant Advanced Non–small Cell Lung Cancer, JAMA Oncology, Vol. 4, No. 5, 2018, pp. 739-742, https://doi.org/10.1001/jamaoncol.2018.0049.